2006
DOI: 10.1107/s0108270106014879
|View full text |Cite
|
Sign up to set email alerts
|

Redetermination of the lanthanum iron sulfide La52Fe12S90

Abstract: A redetermination of the structure of`La 32.66 Fe 11 S 60 ' in the trigonal space group R3m led to the new formula La 52 Fe 12 S 90 and to a rede®nition of the structure type. In the structure, the Fe 2+ cations occur in Fe 2 S 9 dimers of face-sharing octahedra (with 3m symmetry). The dimers are linked by face-and vertex-sharing bi-and tricapped LaS 6 trigonal prisms (with m symmetry) to form a three-dimensional network containing two types of cuboctahedral cavities. The larger cavities remain empty, while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…In contrast, two different coordination environments may be identified for the rareearth cations. Er (1) 13 With the exception of S (11) and S(12), the structure exhibits pseudosymmetry, and therefore similarity restraints were applied to the anisotropic thermal parameters during the least-squares refinements. 17 However, application of Platon/Addsym 27,28 in order to identify missing symmetry elements indicates that there is an additional mirror plane, and that the structure is more correctly described in the centrosymmetric space group Cmcm.…”
Section: Structural Investigationsmentioning
confidence: 99%
“…In contrast, two different coordination environments may be identified for the rareearth cations. Er (1) 13 With the exception of S (11) and S(12), the structure exhibits pseudosymmetry, and therefore similarity restraints were applied to the anisotropic thermal parameters during the least-squares refinements. 17 However, application of Platon/Addsym 27,28 in order to identify missing symmetry elements indicates that there is an additional mirror plane, and that the structure is more correctly described in the centrosymmetric space group Cmcm.…”
Section: Structural Investigationsmentioning
confidence: 99%
“…Structure Determination. Analysis of the products by powder X-ray diffraction on a Siemens D5000 diffractometer revealed that the major phases, Ce 53 Fe 12 S 90 Cl 3 , Ce 53 Fe 12 S 90 Br 3 , and Ce 53 Fe 12 S 90 I 3 , adopt a structure related to the La 52 Fe 12 S 90 type. , While the Ce 53 Fe 12 S 90 I 3 sample was essentially phase pure (to the detection limits), the other samples contained varying amounts of Ce 10 S 14 O and FeS . The cell parameters of the three Ce 53 Fe 12 S 90 X 3 phases, refined by least-squares methods from their powder patterns indexed in R 3̄ m , using the program UNITCELL , are plotted in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…No additional reflection conditions were observed. The centrosymmetric space group R 3̄ m was therefore chosen on the basis of the close relationship between the structures of Ce 53 Fe 12 S 90 X 3 and La 52 Fe 12 S 90 1 Crystallographic Data for Ce 53 Fe 12 S 90 X 3 (X = Cl, Br, I) formulaCe 53 Fe 12 S 90 Cl 3 Ce 53 Fe 12 S 90 Br 3 Ce 53 Fe 12 S 90 I 3 fw 11 088.31 11 221.69 11 362.66 space group R 3̄ m (No.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations